Associations between Parental and Friend Social Support and Children’s Physical Activity and Time Spent outside Playing - Constantinos A. Loucaides; Niki Tsangaridou (International Journal of Pediatrics)
The purpose of this study was to examine the structural validity of a parent and a child questionnaire that assessed parental and friends’ influences on children’s physical activity and investigate the associations between the derived factors, physical activity, and time spent outside. Children (N=154, mean age = 11.7) and 144 of their parents completed questionnaires assessing parental and friends’ influences on children’s physical activity. Children wore a pedometer for six days. Exploratory factor analyses revealed four factors for the parental and five for the child’s questionnaire that explained 66.71% and 63.85% of the variance, respectively. Five factors were significantly associated with physical activity and five significantly associated with time spent outside. Higher correlations were revealed between “general friend support,” “friends’ activity norms,” and physical activity (r=0.343 and 0.333 resp., p<0.001) and between “general friend support” and time spent outside (r=0.460, p<0.001). Obtaining information relating to parental and friends’ influences on physical activity from both parents and children may provide a more complete picture of influences. Parents and friends seem to influence children’s physical activity behavior and time spent outside, but friends’ influences may have a stronger impact on children’s behaviors.